Public Infrastructure Trends and Gaps in Pakistan - Loayza, Norman; Wada, Tomoko (World Bank, Washington, DC, 2014)
This paper analyzes the public infrastructure trends and gaps in Pakistan, especially by placing the Pakistani experience in an international context. It examines the major sectors of public infrastructure, including (a) transportation, (b) telecommunication, (c) electricity generation and (d) water, sanitation and irrigation. Public infrastructure in Pakistan has made some progress over the last five decades. However, compared to other similar countries, the rate of improvement in Pakistan has been among the slowest for the majority of public infrastructure sectors. This has matched the relatively weak economic growth performance of the country in recent decades, which has remained at or below the median country in the world. Moreover the infrastructure improvement has been insufficient to ameliorate substantially the infrastructure conditions of Pakistani citizens.